Using network analysis to explore the key bridge symptoms between posttraumatic stress symptoms and posttraumatic growth among survivors 10 years after the Wenchuan earthquake in China. (June 2022) - Ma, Zijuan; Zhu, Yuanyuan; Tao, Yanqiang; Yang, Zheng; Huang, Shuiqing; Liu, Wenxu; Chen, Yao; Ye, Haoxian; Fan, Fang
Abstract: Despite previous research has illustrated there is high-coexistence between posttraumatic stress disorder (PTSD) and posttraumatic growth (PTG) in the aftermath of traumatic events, few studies have conceptualized the coexistence mechanism of the two psychological phenomena. Using the network analysis, this study aimed to identify the key bridge symptoms and compare sex differences between PTSD symptoms and PTG elements in survivors 10 years after the Wenchuan earthquake in China. A total of 744 survivors 10 years after the Wenchuan earthquake in China completed self-reported questionnaires on demographics, PTSD symptoms (4-item of Posttraumatic Stress Disorder Checklist), and PTG (10-item of Posttraumatic Growth Inventory). Network analysis was used to identify the network structure of PTSD symptoms and elements of PTG, along with bridge symptoms. Additionally, sex differences in the network structure were compared by the Network Comparison Test. Results revealed that the network of PTSD symptoms and elements of PTG was robust to stability and accuracy tests. The key bridge symptoms in the network were "Stronger religious faith", "Changed priorities", and "Easily startled". There were significant differences in network global strength across sex, and network structure across the severity of property loss other than house damage. Future interventions targeting the three key bridge symptoms are expected to relieve the severity of PTSD and promote growth following exposure to traumatic events. Highlights: Three key bridge symptoms linked to PTSD symptoms and PTG elements. Significant differences were found in network properties across sex and the severity of property loss.